Bandeirantes do século XX : trabalhadores da Expedição Roncador-Xingu e Fundação Brasil Central em Nova Xavantina - Santos, Gilberto Brizolla (2011)
The subject this dissertation expose the Roncador-Xingu Expedition’s particularities in front others explored expeditions in the Araguaia Valley and Xingu. These expeditions had objective duple: build knowledge about Central Brazil and produce images that the littoral was civilized and interior Brazil was not. These images were the conception that the government agent of the Roncador – Xingu Expedition had. But, the New Government did not interest in these objectives, but the demographic occupation of the Central Brazil and the military control of this space. The control and the occupation of territories happened with the colonization of the Central Brazil Foundation, with the presence of the National Air Post’s airplanes and the Air Unity Service (Health), together the country people, the aboriginal populations and the military base installed by the Brazilian Air Force in the Serra do Cachimbo and Jacareacanga started to executed the Brazil’s air defense in the Amazonia. The political initiative of the New Government in the Araguaia and Xingu were good, competent and functional. But this politic ha a cost that was not considered in the New Government and nor by the military governments. Among these costs were: the submission of the workers to degrading conditions, the silence produced in the press and in the governmental discourse about these people, and the environmental damage. The social and environmental damages were: river destructions, indiscriminate deforestations, irreversible damages of the biodiversity, rural owners’ constraint and their expulsion to the Amazonian forest, to the periphery of the cities or to the aboriginal cultures and territories that had to reorganize in small areas, as example the Xavante.